Effect of Biological Metacognitive Skills using Project-Based Learning Model - Irda Wahidah Nst; Nurul Hidayah Nasution (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of this study was to determine the effect of biological metacognitive skills taught by a project-based learning model in class X MAS Al-Wasliyah 22 Tembung. The population in this study were all students of class X MAS Al-Wasliyah 22 Tembung which consisted of 3 classes. This type of research uses a quasi-experimental research sample taken by random sampling, namely class X-A with a total of 40 students who are taught using a project-based learning model. The research instrument used a test of metacognitive skills using a questionnaire. The data analysis technique used the t test at a significant level of = 0.05 with the help of SPSS 22.0. The results showed: there was a significant effect on biological metacognitive skills taught by the project-based learning model (thit = 2.05; P = 0.043). The results of biological metacognitive skills that were learned using a project-based model (86.14 ± 3.8) had a significant effect. As a follow-up to the results of this study, it is hoped that teachers can apply project-based learning models to ecosystem materials as an effort to improve the results of metacognitive skills.